Is Ghana Prepared for Another Arboviral Outbreak? Evaluating the 2024 Dengue Fever Outbreak in the Context of Past Yellow Fever, Influenza, and COVID-19 Outbreaks - Godfred Amoah Appiah; Jerry John Babason; Anthony Yaw Dziworshie; Abigail Abankwa; Joseph Humphrey Kofi Bonney (Tropical Medicine and Infectious Disease, 2025)
Arboviruses are a growing concern in many nations. Several reports of arboviral outbreaks have been recorded globally in the past decade alone. Repeated arboviral outbreaks in developing countries have consistently highlighted vulnerabilities in disease surveillance and response systems, exposing critical gaps in early detection, contact tracing, and resource allocation. The 2024 Dengue fever outbreak in Ghana, which recorded 205 confirmed cases out of 1410 suspected cases, underscored the urgent need to evaluate the country’s preparedness for arboviral outbreaks, given the detection of competent vectors in the country. A retrospective analysis of Ghana’s 2009–2013 pandemic influenza response plan revealed significant deficiencies in emergency preparedness, raising concerns about the country’s ability to manage emerging arboviral threats. This review assessed Ghana’s current arboviral outbreak response and preparedness by examining (a) the effectiveness of vector control measures, (b) the role of early warning systems in mitigating outbreaks, (c) laboratory support and diagnostic capabilities, and (d) community engagement strategies. It highlights the successes made in previous outbreaks and sheds light on several gaps in Ghana’s outbreak response efforts. This review also provides recommendations that can be implemented in many countries across Africa as they brace themselves for any arboviral outbreak.